Prose poetry in theory and practice - Caldwell, Anne; Hardwick, Oz (Routledge, an imprint of the Taylor & Francis Group, 2022)
"Prose Poetry in Theory and Practice vigorously engages with the Why? and the How? of prose poetry, a form that is currently enjoying a surge in popularity. With contributions by both practitioners and academics, this volume seeks to explore how its distinctive properties guide both writer and reader, and to address why this form is so well suited to the early 21st century. With discussion of both classic and less well-known writers, the essays both illuminate prose poetry's distinctive features and explore how this 'outsider' form can offer a unique way of viewing and describing the uncertainties and instabilities which shape our identities and our relationships with our surroundings in the early twenty-first century. Combining insights on the theory and practice of prose poetry, Prose Poetry in Theory and Practice offers a timely and valuable contribution to the development of the form, and its appreciation amongst practitioners and scholars alike. Largely approached from a practitioner perspective, this collection provides vivid snapshots of contemporary debates within the prose poetry field, while actively contributing to the poetics and craft of the form"--Provided by publisher.